Strategi Komunikasi Krisis Zulkifli Hasan Menyikapi Isu Deforestasi dan Banjir Sumatra - Mazka Hauzan Naufal; Ismi Dwi Astuti Nurhaeni; Andre Noevi Rahmanto (Universitas Muhammdiyah Yogyakarta, 2026)
This study analyzes Zulkifli Hasan’s crisis communication strategies in response to public attribution of responsibility for the 2025 Sumatra flood disasters, which were linked to his past policies. Utilizing the Situational Crisis Communication Theory (SCCT) framework, this research identifies that although the crisis is categorized as a preventable crisis, which theoretically necessitates a full apology, the subject instead implemented a combination of self-defense strategies. The research findings reveal three primary tactics: (1) Denial through the “attack the accuser